Use of body segments for assess growth and nutritional status in children and adolescents - Maria de las Mercedes Ruiz Brunner; María Elisabeth Cieri; Antonella Melisa Ferrero; María Dania Zárate; Florencia Bainotti; Eduardo Cuestas (Revista de la Facultad de Ciencias Médicas de Córdoba, 2018)
Introduction: Weight and height are essential information to assess growth and nutritional status in pediatrics. The determination of them by direct method is difficult in hospitalized patients. The objective was to analyze the correlation between weight and mid arm circumference (MAC), and between height and knee height (KH) of children and teenagers so it can be used to asses growth and nutritional status in hospitalized children. Population and methods: An observational, descriptive and cross-sectional study was carried out. We included children and teenagers of both gender of 2 and 19 years old. To establish the correlation, the correlation coefficient r and determination R2 were calculated with a significance of p <0.05, plotting the correlation. The MedCalc V12.5.0.0 software was used to analyze the data. Results: Data from 861 subjects were collected. 484 females (56.2% CI95% 52.8-59.5), and 377 males (43.8% CI 95% 40.4-47.2) aged between 2 and 19 years. A correlation was obtained between the KH and the height of r = 0.98 for both sexes, (R2 = 0.96 females and R2 = 0.97 in males), p <0.001. The MAC showed a correlation with the weight of r = 0.92 (R2 = 0.76) in males and r = 0.87 (R2 = 0.85) in females, both with p <0.001. Conclusions: Body segments KH and MAC have a high correlation with height and weight, respectively. That is why we propose to use them for the assessment of growth and nutritional status in hospitalized children with functional limitations.